2011
DOI: 10.1007/s11224-011-9741-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure, pKa, lipophilicity, solubility, absorption, polar surface area, and blood brain barrier penetration of some antiangiogenic agents

Abstract: The methods of theoretical chemistry have been used to elucidate molecular properties of selected and novel antiangiogenic agents (semaxanib, sunitinib, N-methylsunitinib, sorafenib, motesanib, ABT-869, vatalanib, vandetanib, AEE 788, CP-547632, A-1, A-2, A-3, and A-4). The geometries and energies of these drugs have been computed using HF/6-31G(d), Becke3LYP/6-31G(d) and Becke3LYP/ 6-31??G(d,p) model chemistries. Wherever possible the most stable conformations of inhibitors studied are stabilized by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Figure 1B depicts the MS features as well as some key properties for all SANs. Although the lipophilicity of sunitinib variants (SANs 1-5) was decreased compared with sunitinib, the polar surface area remained unaffected (<100 Å 2 ) for all SANs, a parameter known to influence cell membrane permeability (35). A representative mass spectrum and LC/MS-MS chromatogram for a chosen analogue (SAN1) can be found in Supplementary Information Section S2.…”
Section: Synthesis Of Sansmentioning
confidence: 99%
“…Figure 1B depicts the MS features as well as some key properties for all SANs. Although the lipophilicity of sunitinib variants (SANs 1-5) was decreased compared with sunitinib, the polar surface area remained unaffected (<100 Å 2 ) for all SANs, a parameter known to influence cell membrane permeability (35). A representative mass spectrum and LC/MS-MS chromatogram for a chosen analogue (SAN1) can be found in Supplementary Information Section S2.…”
Section: Synthesis Of Sansmentioning
confidence: 99%
“…In the following study, Remko et al [172] used ab initio methods to study molecular structure, lipophilicity, solubility, absorption, and blood-brain barrier penetration of some novel antiangiogenic agents (semaxanib, sunitinib, N-methylsunitinib, sorafenib, motesanib, ABT-869, vatalanib, vandetanib, AEE 788, CP-547632, A-1, A-2, A-3, and A-4). The results show that, whenever possible, the most stable conformers are stabilized by intramolecular hydrogen bonds.…”
Section: Issuementioning
confidence: 99%
“…Additionally, several studies have reported the effect of lipophilicity on biological activities and transport properties [1][2][3][4][5][6][7], indicating the importance to evaluate the lipophilicity of new drugs or pro-drugs. Thus, an eligible drug usually needs to keep a balance between lipophilicity and hydrophilicity to dissolve in the body fluid and penetrate the biofilm effectively.…”
Section: Introductionmentioning
confidence: 99%
“…The lipophilicity of a compound can be quantitatively characterized by the partition coefficient (its logarithm form is denoted as logP) or the distribution coefficient (its logarithm form is denoted as logD) if ionized molecular species are present [4,5]. Partition coefficient [8] is the equilibrium concentration ratio of the solute between two immiscible solvents (e.g., n-octanol and water).…”
Section: Introductionmentioning
confidence: 99%